2006
DOI: 10.1098/rspb.2006.3653
|View full text |Cite
|
Sign up to set email alerts
|

Himalayan porter's specialization: metabolic power, economy, efficiency and skill

Abstract: Carrying heavy loads in the Himalayan region is a real challenge. Porters face extreme ranges in terrain condition, path steepness, altitude hypoxia and climate for 6-8 h a day, many months a year, since they were boys. It has been previously shown that, when carrying loads on level terrain, porters' metabolic economy is higher than in Caucasians but the reasons are still unknown. We monitored Nepalese porters both during 90 km trekking in Khumbu Valley and at two different altitudes (3490 and 5050 m above sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 19 publications
(38 reference statements)
2
46
0
1
Order By: Relevance
“…Our results have been echoed by the on-field load-carrying measurements of Minetti et al (2006) in the Khumbu valley in Nepal. They highlighted the higher efficiency of the Nepalese porters compared with trained Caucasian mountaineers during both uphill and downhill loaded walking.…”
Section: Muscular Efficiencysupporting
confidence: 63%
See 2 more Smart Citations
“…Our results have been echoed by the on-field load-carrying measurements of Minetti et al (2006) in the Khumbu valley in Nepal. They highlighted the higher efficiency of the Nepalese porters compared with trained Caucasian mountaineers during both uphill and downhill loaded walking.…”
Section: Muscular Efficiencysupporting
confidence: 63%
“…2). With the exception of the porters in the low flatlands, the Nepalese typically walk on very hilly terrain where there are hardly ever two steps taken at the same level (Minetti et al, 2006). In preliminary experiments in our laboratory, we have found that a change in height within one step of only 0.09 m (equivalent to a grade of ∼10%) is sufficient to decrease R from 64.4±2.4% to 36.9± 8.6% (mean±s.d., n=12) at ∼1.35 m s −1…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The head strap method has received some recent attention. Minetti et al (2006) concluded that the remarkable capabilities of the Himalayan porters could only partially be explained by metabolic efficiency whilst Malville et al (2001) argued that a combination of pacing strategy and metabolic efficiency contribute to the load carrying abilities of the commercial porters in Eastern Nepal. Both studies seem to support the early findings of Nag et al (1979) who reported this method as being particularly economical when heavy loads are carried at relatively slow speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Indian soldiers are compelled to carry load manually as wilderness of the high altitude terrains construct a critical barrier to the vehicular mode of transportation of load (1). Indian Army deploys more than hundred thousand soldiers in the high altitude border areas.…”
Section: Introductionmentioning
confidence: 99%